2018
DOI: 10.1080/09168451.2018.1438168
|View full text |Cite
|
Sign up to set email alerts
|

Acute supplementation of valine reduces fatigue during swimming exercise in rats

Abstract: We investigated the respective effects of the acute supplementation of valine, leucine, and isoleucine on metabolism-related markers by administering a swimming exercise test to rats. As a behavioral analysis, we evaluated the effect of valine and that of leucine on spontaneous activity after exercise. Acute supplementation of valine before exercise significantly suppressed the depression of the liver glycogen and the blood glucose after exercise, whereas leucine decreased the blood glucose and isoleucine had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Cortisol breaks down muscle or liver glycogen to maintain the blood glucose level when blood glucose levels decrease [ 33 , 34 ]. It was reported that acute valine supplementation maintained the liver glycogen content and suppressed the cortisol level in rodents [ 26 ]. These findings suggest that muscle or liver glycogen might be maintained by the AA mixture supplement in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cortisol breaks down muscle or liver glycogen to maintain the blood glucose level when blood glucose levels decrease [ 33 , 34 ]. It was reported that acute valine supplementation maintained the liver glycogen content and suppressed the cortisol level in rodents [ 26 ]. These findings suggest that muscle or liver glycogen might be maintained by the AA mixture supplement in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that arginine administration promoted lipid metabolism in rodents and humans [ 23 25 ], which might lead to the maintenance of glucose or glycogen levels during exercise and therefore suppress the cortisol increase. The acute supplementation of valine is reported to effectively decrease the level of glucocorticoid (corticosterone in rodents) by maintaining liver glycogen and blood glucose in a rodent study [ 26 ]. Serine is known as a substrate in the production of phosphatidylserine, which is reported to blunt the increases in cortisol levels during exercise [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to L-leucine and L-isoleucine, the few studies on the effects of valine on blood glucose have yielded inconsistent findings [22]. In fasted rats, L-valine (0.3 g/kg body weight, equivalent to ~22.5 g in a 75 kg human), given orally 30 min before an oral glucose tolerance test, increased plasma glucose levels, 60 min later by ~20 mg/dl [38], and, at a dose of 1 g/kg body weight, ameliorated the fall in blood glucose induced by exercise [39], while, in contrast, intrahypothalamic infusion of L-valine (12 nmol), given with a continuous intravenous glucose infusion, was reported to lower blood glucose [40], compared with control rats. In fasted healthy humans, intravenous administration of 30 g L-valine resulted in a small stimulation of insulin secretion and decrease in blood glucose concentrations [21].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have confirmed that increasing glycogen levels may alleviate fatigue; for example, hydrogen water drinking relieves fatigue by lowering blood sugar, lactic acid, BUN, and increasing liver glycogen [56]. In the mouse swimming experiment, acute valine supplementation helps maintain liver glycogen and blood sugar levels and increases spontaneous activity, which could contribute to relieving postexercise fatigue [57]. For a long time, people have tried to adopt traditional Chinese medicine methods such as Ginseng and fungus to treat fatigue and achieved good results.…”
Section: Discussionmentioning
confidence: 99%